Adenovirus Methods and Protocols Volume 1: Adenoviruses, Ad Vectors, Quantitation, and Animal Models - Wold, William S. M.; Tollefson, Ann E.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Adenovirus Methods and Protocols, Second Edition, now in two volumes, is an essential resource for adenovirus (Ad) researchers beginning in the field, and an inspirational starting point for researchers looking to branch into new areas of Ad study. In addition to updating and expanding important chapters from the first edition, the authors have added new chapters that address innovative, exciting areas of emphasis in Ad research, including Ad vector construction and use, real-time PCR, use of new animal models, and methods for quantification of Ad virus or virus expression/interactions. Each of the protocols presented in these volumes is written by trendsetting researchers in their respective areas of expertise. Volume 1 addresses several important techniques for construction of adenoviruses for use as vectors and for basic research. Highlighted topics include deletion mutants, capsid modifications, insertions, and gene replacements in human, murine, bovine, and ovine adenoviruses. In Volume 2, the authors focus on methods that elucidate and quantitate the interactions of Ad with the host. Each of the protocols in these volumes provides a general introduction, followed by tried-and-true step-by-step methods. Both novice and experienced researchers will reap tremendous benefit from these groundbreaking volumes in Ad research.
Manipulation of Early Region 4 -- Isolation, Growth, and Purification of Defective Adenovirus Deletion Mutants -- Construction of Adenovirus Type 5 Early Region 1 and 4 Virus Mutants -- Construction of Mouse Adenovirus Type 1 Mutants -- Generation of Recombinant Adenovirus Using the Escherichia coli BJ5183 Recombination System -- Production and Release Testing of Ovine Atadenovirus Vectors -- Construction of Capsid-Modified Recombinant Bovine Adenovirus Type 3 -- Adenovirus Capsid Chimeras -- Temperature-Sensitive Replication-Competent Adenovirus shRNA Vectors to Study Cellular Genes in Virus-Induced Apoptosis -- Evaluating Apoptosis in Tumor Cells Infected With Adenovirus Expressing p53 Tumor Suppressor Gene -- Growth and Purification of Enteric Adenovirus Type 40 -- Immunocompetent, Semi-Permissive Cotton Rat Tumor Model for the Evaluation of Oncolytic Adenoviruses -- Use of the Syrian Hamster as an Animal Model for Oncolytic Adenovirus Vectors -- A Real-Time PCR Method to Rapidly Titer Adenovirus Stocks -- Detection and Quantitation of Subgroup C Adenovirus DNA in Human Tissue Samples by Real-Time PCR -- Flow Cytometric Detection of Adenoviruses and Intracellular Adenovirus Proteins -- Capture ELISA Quantitation of Mouse Adenovirus Type 1 in Infected Organs -- Preparation and Titration of CsCl-Banded Adenovirus Stocks.
Keywords: Virology; Cell biology; Human genetics; Oncology .; Virology; Cell Biology; Human Genetics; Oncology